Optimizing the Utilization of GoFood System Application as an Income Enhancement at Rungkut Surabaya MSME - Invony Dwi Aprilisanda; Devy Sylvia Puspitasaria; Luqita Romaisyah (Journal of Economics, Business, and Government Challenges, 2020)
In the digital age, technological developments are moving very fast and changingthe lifestyle of humans in general. The technological system in the Digital Ageattracted the interests of culinary MSME entrepreneurs in Indonesia to do businesswith an online sales system. One of the online food delivery service applications inIndonesia is GoFood, this study aims to find out how SMEs in Surabaya asGoFood partners can increase their income by optimizing the use of the GoFoodapplication. This study uses a qualitative method. Data analysis in this research isdescriptive qualitative. Criteria for selecting informants using purposive samplingtechniques. The interview results state that the GoFood application tends to beeasy to use, but some partners regretted the lack of training which resulted in salesnot meeting expectations. Quality, Quality, Promo Price, and timeliness of foodprocessing to food delivery to consumers is a strategy for GoFood merchantpartners to optimize their sales turnover.